Different Outcomes of “Silent Hypoxia” in Patients with COVID-19 Pneumonia: A Case Series and Literature Review - Ashani Ratnayake; Prabhashini Kumarihamy; Sujeewa Gunaratne; Hiranya Abeysinghe; Sahan Perera; Shirley Ekanayake (Case Reports in Critical Care)
COVID-19 has been declared a pandemic since March 2020 and it has been responsible for millions of deaths worldwide. The SARS-CoV-2 causes a spectrum of diseases mainly affecting the respiratory system. It can also complicate other systems causing thromboembolic phenomena and myocardial ischaemia. An entity of hypoxia has been described in these patients which show no clinical signs and symptoms of respiratory distress despite being extremely hypoxic. This is called silent or happy hypoxia. The exact mechanism for this is not known. We report 4 cases which had similar presentations of silent hypoxia but had different course of illness and different outcomes. All 4 patients did not show any signs of respiratory distress, but had oxygen saturation less than 82%. 3 of them needed intensive care unit support for oxygen therapy and subsequently needed noninvasive ventilation. Only one required invasive ventilation. The fourth patient did not require intensive care support. The patient who required invasive ventilation succumbed due to severe COVID pneumonia whereas the other 3 patients were discharged from the hospital. Silent hypoxemia can go undetected in COVID-19 patients particularly in the time of a pandemic. This case series highlights the importance of meticulous clinical examination including oxygen saturation measurements in suspected or confirmed patients with COVID-19. The course of illness can be different in different populations, and this needs further clinical evidence.